Attitudes of Louisiana practitioners toward rehabilitation of juvenile offenders - Moak, Stacy C. (American journal of criminal justice, 2000)
This study addresses attitudes of juvenile justice practitioners in Louisiana toward rehabilitation. A statewide survey was mailed to 3,947 lawyers, judges, probation officers, social workers, and volunteer coordinators. Respondents were grouped by legal training and casework training. Conclusions indicate Louisiana practitioners have not abandoned the concept of rehabilitation for juvenile offenders. However, they do support punishment as a viable option when treating offenders. Furthermore, job descriptions are less important in determining support for rehabilitation than are demographic variables. In addition, perceptions of juvenile crime also help shape these opinions.